Haemolymph constituents and osmolality as functions of moult stage, body weight, and feeding status in marron, Cherax cainii (Austin and Ryan, 2002) and yabbies, Cherax destructor (Clark, 1936) - Van Mai, H.; Fotedar, Ravi (Elsevier BV, 2018)
The study investigates the change in osmolality and haemolymph constituents in marron Cherax cainii and yabbies Cherax destructor associated with moult stages, body weights and their feeding status. A total of 582 haemolymph samples from 5 moult stages (postmoult-AB, intermoult-C, and premoult stages – D0, D1, D2), two body weight classes (2–15 g and 61–75 g) and nutritional status were used for analysis of osmolality, protein, glucose, and ionic concentrations of potassium and chloride following the standard biochemical procedures. The haemolymph protein, glucose, potassium and chloride levels were highest at intermoult and early premoult stages, and lowest at postmoult in both crayfish species. Except protein, no significant differences were seen in analyzed parameters between various weight classes and two species. Haemolymph osmolality, protein and glucose were significantly higher in fed crayfish, whereas no variations in haemolymph potassium and chloride concentrations were observed between the fed and unfed crayfish. Maximum osmolality was recorded at 7–8 h after feeding in both crayfish species. The results showed that the biochemical changes in the haemolymph of marron and yabbies are related to moult stages, body weight and feeding and thus can be used as tools for determining suitable diets.